Innovation Pattern of Employee work Barebbo Subdistrict Bone Regency - Aslinda, Aslinda; Siraj, Muhammad Luthfi; Tadampali, Andi Caezar To (Pinisi Business Administration Review, 2023)
This study aims to determine the work innovation of employees in the Barebbo District office, Bone Regency, using a qualitative design approach. This type of research is descriptive qualitative by using observation, interview, and documentation techniques in data collection. The key informants of this research are the sub-district head, the head of the section and the community with data analysis techniques used, namely data condensation, data display or data presentation, and verification or conclusions. The results showed that the innovation of the work of the state civil apparatus at the Barebbo sub-district office was innovated quite well. This means that employees in Barebbo, Bone Regency, have shown and carried out various innovations in carrying out their work duties by utilizing all computer technology to work more easily, quickly and precisely. In addition, other forms of innovation are to design standard operating procedures that are easier and clearer and to innovate in work attitudes by always saving materials and reducing costs used for work.